Opportunities for Youth and Women’s Participation in Ghana’s Labour-intensive Public Works Program - Dadzie, Christabel E.; Ofei-Aboagye, Esther (World Bank, Washington, DC, 2021)
Ghana’s public works program, Labour-Intensive Public Works (LIPW), was initiated in 2010 with the goal of providing short-term employment opportunities to the poorest and building community assets. Public works programs have the potential to promote social inclusion by benefiting vulnerable groups, particularly youth and women. The LIPW program in its operational design, included provisions to support women workers, including having on-site crèches and latrines and provided flexibility of employment so that women could easily access the program. Although, the program did not exclude qualified youth, operational designs did not lay emphasis on youth engagement. The LIPW program could be positioned as a youth employment avenue, as well as promoting social inclusion and enhancing the overall well-being of its beneficiaries. As such, this study reviews the operational opportunities within the Ghana LIPW program design targeting women and youth and provides recommendations for enhancing social inclusion for these groups in future programming. This study will be useful for public works program implementers, as well as policy makers, looking to boost social inclusion within their programming.